Brief Cases More Stories From the Dresden Files - Butcher, Jim, 1971- (New York Ace, 2018)
"An all-new Dresden Files story headlines this urban fantasy short story collection starring the Windy City's favorite wizard. The world of Harry Dresden, Chicago's only professional wizard, is rife with intrigue--and creatures of all supernatural stripes. And you'll make their intimate acquaintance as Harry delves into the dark side of truth, justice, and the American way in this must-have short story collection. From the Wild West to the bleachers at Wrigley Field, humans, zombies, incubi, and even fey royalty appear, ready to blur the line between friend and foe. In the never-before-published "Zoo Day," Harry treads new ground as a dad, while fan-favorite characters Molly Carpenter, his onetime apprentice, White Council Warden Anastasia Luccio, and even Bigfoot stalk through the pages of more classic tales. With twelve stories in all, Brief Cases offers both longtime fans and first-time readers tantalizing glimpses into Harry's funny, gritty, and unforgettable realm, whetting their appetites for more to come from the wizard with a heart of gold. The collection includes: *"Curses", from THE NAKED CITY, edited by Ellen Datlow *"AAAA Wizardry", from the Dresden Files RPG *"Even Hand", from DARK AND STORMY KNIGHTS, edited by P.N. Elrod *"B is for Bigfoot", from UNDER MY HAT: TALES FROM THE CAULDRON, edited by Jonathan Strahan. Republished in WORKING FOR BIGFOOT *"I was a Teenage Bigfoot", from BLOOD LITE 3: AFTERTASTE, edited by Kevin J. Anderson. Republished in WORKING FOR BIGFOOT. *"Bigfoot on Campus", from HEX APPEAL, edited by P.N. Elrod. Republished in WORKING FOR BIGFOOT. *"Bombshells", from DANGEROUS WOMEN, edited by George R.R. Martin and Gardner Dozois *"Jury Duty", from UNBOUND, edited by Shawn Speakman *"Cold Case", from SHADOWED SOULS, edited by Jim Butcher and Kerrie Hughes *"Day One", from UNFETTERED II, edited by Shawn Speakman *"A Fistful of Warlocks", from STRAIGHT OUTTA TOMBSTONE, edited by David Boop *"Zoo Day"--Brand-new novella, original to this collection"--
Fistful of warlocks -- B is for Bigfoot -- AAAA wizardry -- I was a teenage Bigfoot -- Curses -- Even hand -- Bigfoot on campus -- Bombshells -- Cold case -- Jury duty -- Day one -- Zoo day.
107224
Keywords: Dresden, Harry -- (Fictitious character) -- Fiction; Wizards -- Fiction; Short stories; Fiction -- Fantasy -- Urban Life; Fiction -- Short Stories (single author); Fantasy fiction; Short stories